EVALUATING THE CONTRIBUTION OF THE EUROPEAN UNION IN INVESTMENTS IN MUNICIPAL ECONOMY AND ENVIRONMENTAL PROTECTION. EXAMPLE OF COMMUNES IN THE WIELKOPOLSKIE VOIVODESHIP - Aldona Standar; Natalia Bartkowiak-Bakun (Journal of Agribusiness and Rural Development, 2015)
The article presents the level, dynamics and structure of expenditure in communes after 2004. Particular attention was focused on the expenditure allocated to the category of budget classifi cation: Municipal economy and environmental protection. The survey subjects were all communes: urban, urban-rural and rural in the Wielkopolskie voivodeship. In conclusion, in 2004–2012 there were major changes in spending funds by communes in Wielkopolska region. It should be noted that in rural communes more funds, than on much-needed expansion of water supply and sewerage systems, are spent on transport, agriculture, and education and upbringing. Given the capital-intensive nature of this type of investment, much of it will not be realised if EU funds are not obtained.